2019
DOI: 10.1051/0004-6361/201935550
|View full text |Cite
|
Sign up to set email alerts
|

Lyman continuum escape fraction and mean free path of hydrogen ionizing photons for brightz∼ 4 QSOs from SDSS DR14

Abstract: Context. One of the major challenges in observational cosmology is related to the redshift evolution of the average hydrogen (HI) ionization in the Universe, as evidenced by the changing in the ionization level of the intergalactic medium (IGM) through cosmic time. In particular, starting from the first cosmic reionization, the rapid evolution of the IGM physical properties poses severe constraints for the identification of the sources responsible for keeping its high level of ionization up to lower redshifts.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 64 publications
2
55
0
Order By: Relevance
“…This enhancement in the ionization level of the IGM due to the ionizing QSO flux extends to several proper Mpc (∼ 6 − 10 pMpc) as observed in bright QSOs (M 1450 −27; Fan et al 2006;Calverley et al 2011;Eilers et al 2017). This implies that their escape fraction is in general relatively large (∼ 70%) and appears to keep values > 50% in fainter AGNs (M 1450 −23; Cristiani et al 2016;Grazian et al 2018;Romano et al 2019). Thus, the relevance of AGNs in the reionization process mainly depends on the space density evolution of AGNs with M 1450 < −22 in the redshift interval 3.5 < z < 6.5.…”
Section: Introductionmentioning
confidence: 54%
“…This enhancement in the ionization level of the IGM due to the ionizing QSO flux extends to several proper Mpc (∼ 6 − 10 pMpc) as observed in bright QSOs (M 1450 −27; Fan et al 2006;Calverley et al 2011;Eilers et al 2017). This implies that their escape fraction is in general relatively large (∼ 70%) and appears to keep values > 50% in fainter AGNs (M 1450 −23; Cristiani et al 2016;Grazian et al 2018;Romano et al 2019). Thus, the relevance of AGNs in the reionization process mainly depends on the space density evolution of AGNs with M 1450 < −22 in the redshift interval 3.5 < z < 6.5.…”
Section: Introductionmentioning
confidence: 54%
“…While a skewed distribution of free paths along individual lines of sight is expected (e.g. Romano et al 2019), and while this particular QSO is the brightest (and lowest redshift) one in our ESI + X-Shooter sample, a larger sample at z ∼ 6 would help to characterize the spatial variations in ionizing opacity near the end of reionization. Given the rapid increase in λ mfp between z = 6 to 5, and the different evolutions predicted by the models over this redshift range (e.g.…”
Section: Implications For Reionizationmentioning
confidence: 90%
“…They find values that are ∼10-20 per cent higher than those of Prochaska et al (2009) and Worseck et al (2014) over the same redshifts. In trials using the two lower redshift GGG composites from Worseck et al (2014) we found that this discrepancy is well explained by the lack of foreground Lyman series absorption in the Romano et al (2019) analysis. Worseck et al (2014) fit a power law of the form λ mfp (z) ∝ (1 + z) −5.4 over 2.44 < z < 5.16 (dotted line in Fig.…”
Section: Fits To the Datamentioning
confidence: 92%
See 2 more Smart Citations